The Influence of HRM Audit and Transformational Leadership on Employee Performance at Rafflesia Bengkulu Hospital - Asyifa, Fitria; Ratnawili, Ratnawili (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
This study aims to determine the effect of HRM audit and transformational leadership on employee performance at Rafflesia Bengkulu Hospital. This type of research uses a quantitative descriptive research method. The number of respondents in this study amounted to 90 people. The data collection method uses a questionnaire and uses analytical techniques using multiple linear regression analysis tests and hypothesis testing, namely the t test and f test. Based on the results of multiple linear regression, the regression equation 2.162 + 0.344X1+ 0.291X2 and the results of the t test and f test of this study can be concluded that HRM audit has a significant effect on employee performance, this is evidenced by the results of the t test showing the value of tcount > thitung > ttabel (6.239 > 1.663) and (sig α = 0.00 < 0.05). This means H_0 is rejected and H_a is accepted. Transformational Leadership has a significant effect on Employee Performance, this is evidenced by the results of the t test showing tcount > thitung > ttabel thitung > ttabel (4.531 > 1.663) and (sig α = 0.00 < 0.05). This means H_0 is rejected and H_a is accepted. HRM Audit (X1) and Transformational Leadership (X2) together have a significant effect on Employee Performance (Y) at Rafflesia Hospital Bengkulu City, this is evidenced by the F test showing the value of fcount > ftable , namely fhitung > ftabel , yaitu yaitu (110.033 > 3.10) dan (sig α = 0.000 < 0.05). This means H_0 is rejected and H_a is accepted.